History of the Arab invasions - Belâzürî, ?- 892/93. (London ; New York)
x, 576 sayfa, [4] sayfa harita
Keywords: “Ahmad bin Yahuya al-Baladhuri's History of the Arab Invasions is perhaps the most important single source for the history of the great Arab conquests of the Middle East in the sixth and early seventh centuries. The author, who died in 892, was a historian working at court of the Abbasid caliphs in Baghdad. He had access to a wide variety of earlier writings on the conquests and has preserved accounts that are not found anywhere else. But the book is much more than a series of accounts of battles. Baladhuri was very interested in the origins of the Islamic state and its institutions. His work contains a wealth of information about government, land-holding and economic developments. It is, in short, a key text for anyone interested in the formation of the Islamic world. In this new modern translation, fully annotated with a scholarly apparatus and commentary on the places, events and individuals mentioned, a key source on the Arab conquests is made available in English. It will be essential reading for scholars and students of Islamic Studies and Middle East history.” --